Chile : Toward a Cohesive and Well Governed National Innovation System - World Bank (Washington, DC, 2017)
Chile is increasingly looking to innovation as a pillar of its competitiveness and an engine of growth to close the income gap with the Organization for Economic Cooperation and Development (OECD) economies. The country has doubled its per capita income since the 1990s. The growth slowdown in the late 1990s and early 2000s, however, raised concerns about that the old sources of growth. While the rate of growth has picked up again, spurred by a favorable external environment, there is an increased awareness of the importance of innovation to growth and a desire to move toward a more diversified and knowledge-based economy, following the example of other successful resource-rich economies such as Australia and Finland. Higher government commitments to innovation have raised new challenges. The remaining of the report is structured as follows. Chapter two discusses the importance of innovation to Chile's economy and highlights the need to define innovation policy within a comprehensive framework that encompasses the entire production system. Chapter three organizes thinking around some basic governance principles for innovation systems drawing form the public governance literature, the broader innovation literature, and international experiences. Chapter four applies those principles to Chile's public institutions and agents that will be responsible for defining and implementing innovation policies. Chapter five examines the rationale and guiding principles of regional innovation policies and offers recommendations for Chile's regional innovation systems and their governance framework. Chapter six summarizes the main conclusions.